Новый для науки вид слизня рода Deroceras (Gastropoda, Limacidae) из Крыма - Скляр, И.Я. (Вестник зоологии, 1975)
A new for science species of slug Deroceras (Liolytopelte) hamatum sp. n. is described. It differs from the closest spices D. (L.) caucasica Simr. in the peculiarities of the structure of the penis lime plate and other characters, especially in the body size. The new slug was found in the forest zone of the Crimea mountains.